2012
DOI: 10.1167/iovs.11-8053
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Toxicological Effects of Cefuroxime on the Albino Rabbit Retina

Abstract: ERG and histologic findings indicated that a dose of 1 mg cefuroxime, administered intravitreally, was not toxic to the rabbit retina. A dose of 10 mg, injected intravitreally, induced transient physiological effects, and was toxic to the rabbit retina, as was evident by the permanent reduction in the ERG responses and by the structural damage to the retina with signs of glial activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
0
21
0
8
Order By: Relevance
“…While doses as low as 10 mg injected into the vitreous in rabbits have induced structural changes to the retina, 14 no reports as yet show deleterious clinical effects in humans at this dose. This is the first report, to our knowledge, of the effects on the human eye of intracameral injection of cefuroxime sodium at a dose of 9 mg.…”
Section: Discussionmentioning
confidence: 99%
“…While doses as low as 10 mg injected into the vitreous in rabbits have induced structural changes to the retina, 14 no reports as yet show deleterious clinical effects in humans at this dose. This is the first report, to our knowledge, of the effects on the human eye of intracameral injection of cefuroxime sodium at a dose of 9 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes present in the central nervous system, retina, and optic nerve head were previously thought to be bystander cells, but clearly in the past few years various studies have indicated that they play important roles such as regulation of ionic balance, neurotransmission, synaptic plasticity, and neurodegeneration (39). GFAP is an intermediate filament that is normally expressed in astrocytes but not Müller cells in the retina (34,40). However, in a variety of retinal injuries such as retinal detachment (41), ischemia (42), and increased intraocular pressure (43), GFAP expression in retinal Müller cells became evident (34).…”
Section: Discussionmentioning
confidence: 99%
“…GFAP is an intermediate filament that is normally expressed in astrocytes but not Müller cells in the retina (34,40). However, in a variety of retinal injuries such as retinal detachment (41), ischemia (42), and increased intraocular pressure (43), GFAP expression in retinal Müller cells became evident (34). Because of this, GFAP expression in Muller cells has been widely used as a molecular indicator of retinal stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations